2015
DOI: 10.1002/eji.201445405
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Wntless in endosteal niches impairs lymphopoiesis rather than HSCs maintenance

Abstract: Osteoblasts and perivascular stromal cells constitute essential niches for HSC selfrenewal and maintenance in the bone marrow. Wnt signaling is important to maintain HSC integrity. However, the paracrine role of Wnt proteins in osteoblasts-supported HSC maintenance and differentiation remains unclear. Here, we investigated hematopoiesis in mice with Wntless (Wls) deficiency in osteoblasts or Nestin-positive mesenchymal progenitor cells, which presumptively block Wnt secretion in osteoblasts. We detected defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…Depletion of Col2.3 + osteoblastic cells resulted in reduced B lymphopoiesis preceding a reduction in LSKs (Zhu et al, 2007). Disruption of Wntless or Gsα signaling using Col1 -Cre or Osterix ( Osx )-Cre respectively also led to impaired B cell development (Cao et al, 2015, Wu et al, 2008). Depletion of Osteocalcin (OCN) + osteolineage cells or deletion of Dll4 in OCN + cells reduced CLP numbers, T lymphopoiesis without overtly impairing the HSC compartment (Yu et al, 2015).…”
Section: Hierarchical Differentiation Hierarchical Niche?mentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of Col2.3 + osteoblastic cells resulted in reduced B lymphopoiesis preceding a reduction in LSKs (Zhu et al, 2007). Disruption of Wntless or Gsα signaling using Col1 -Cre or Osterix ( Osx )-Cre respectively also led to impaired B cell development (Cao et al, 2015, Wu et al, 2008). Depletion of Osteocalcin (OCN) + osteolineage cells or deletion of Dll4 in OCN + cells reduced CLP numbers, T lymphopoiesis without overtly impairing the HSC compartment (Yu et al, 2015).…”
Section: Hierarchical Differentiation Hierarchical Niche?mentioning
confidence: 99%
“…Cre recombinase transgenic strains developed to target osteoblasts or osteocytes, such as Ocn -Cre (Yu et al, 2015) or Dmp1 -Cre (Sato et al, 2013), are now known to also target various portions of BM MSCs (Zhang and Link, 2016). However, HSPCs were mostly spared in some of these models despite the severe lymphoid defects at least at the time of analysis, suggesting that the lymphoid progenitors might have a different niche requirement or distinct sensitivity to niche regulations than HSCs (Cao et al, 2015, Yu et al, 2015). Indeed, during inflammation, lymphoid progenitors are the first to be depleted from the BM to allow emergency granulopoiesis, possibly due to their different requirement for niche retention factors such as CXCL12 (Ueda et al, 2005, Ueda et al, 2004).…”
Section: Hierarchical Differentiation Hierarchical Niche?mentioning
confidence: 99%
“…Of interest, deletion of the Wntless gene (Wls), which is functionally related to Porcn as it also is required for secretion of Wnt proteins, shows a hematopoietic and lymphopoietic phenotype when deleted from osteoblastic niche cells. (48) Moreover, work in Drosophila has demonstrated that non-secreted Wnts might still have a function, shedding a somewhat different light on the absolute requirement of Wnt secretion (49). Whatever the reason, the levels of Axin2 and other Wnt target genes were not affected by Porcn deletion in hematopoietic cells (46), hence no loss-of function model for Wnt signaling was generated.…”
Section: Loss Of Function (Lof) Studies For Wnt Signaling In Hematopomentioning
confidence: 97%
“…Recent findings show that inactivation of wintless (WLS, a mediator of WNT ligands secretion) in OBs impairs B‐cell lymphopoiesis and affects T‐lineage cells. This mutation led to a reduction in the frequency of ETPs in the thymus and to mature naive T‐cell infiltration in the BM rather than spleen . Thus, although studies have revealed common microenvironmental cues shared between HSCs and progenitors, most of the extrinsic signals regulating lymphoid progenitor commitment and differentiation appear to be specific to this compartment, suggesting the existence of different niches with specialized function in the BM ( Fig.…”
Section: The Role Of the Bm Niche In Regulating Hematopoietic Stem Anmentioning
confidence: 98%